The process of coping with cyberbullying: A systematic review. (July 2015) - Raskauskas, Juliana; Huynh, Amanda
Abstract: Cyberbullying is an established threat to the well-being of youth worldwide. How victims cope with cyberbullying has the potential to buffer against negative effects. The present study is a systematic review of research on coping with cyberbullying to identify whether the process of coping is being used to identify pathways to resilience. In this review the process of coping with cyberbullying, the Transactional Model of Stress and Coping, and to what degree existing studies have examined the process of coping were considered. Findings indicated that much of the prior literature has identified components of the process but few studies have looked at the process itself. Understanding the process of coping with cyberbullying has important implications for how victims appraise the threat of cyberbullying, select coping strategies, and perceive their ability to enact those strategies (self-efficacy). The need for additional research and an explanation of how a better understanding of the process is needed to design effective cyberbullying interventions are discussed. Highlights: It is a systematic review of coping with cyberbullying studies for pathways to resilience. Transactional Model of Stress and Coping was used to examine the coping process. It was found that literature has studied components of coping but not the entire coping process. How victims appraise cyberbullying and select coping strategies needs more research. Self-efficacy is an overlooked part of the cyberbullying coping process. A process model for coping with cyberbullying for future research is proposed.